Nilai Didaktis dalam Novel Nonik Jamu Karya Rina Suryakusuma - Umi Faizah; Nian Diani Indrafuri; Lia Safira; Suryanti Suryanti; Nadia Widodo (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to describe the didactic values contained in the novel Nonik Jamu by Rina. The method used in this study is a qualitative descriptive method with a data source in the form of the novel Nonik Jamu by Rina Suryakusuma. The data collection technique used is the note-taking technique. The focus of this research study is the didactic values that appear in the plot, characters, and conflicts that shape the development of characters in the story. The results of the study show 12 didactic values contained in the novel, namely the values of helping others, empathy, honesty, tolerance, respect for others, persistence and tenacity, sharing, usefulness, repaying evil with goodness, prioritizing good from bad, danger of evil, and the quality of good deeds. These values are conveyed subtly through the experiences of the main characters in dealing with various life problems, so as to provide moral lessons that are easy for readers to understand. This research has many benefits for life because the values found can be used as character learning materials in daily life. This novel also emphasizes the importance of courage, sincerity, and strong determination in facing social challenges, thus inspiring readers to be wiser in their attitudes and actions.